Prolonged Tpeak-Tend interval is associated with ventricular fibrillation during reperfusion in ST-elevation myocardial infarction. (1st April 2019) - Demidova, M.M.; Carlson, J.; Erlinge, D.; Azarov, J.E.; Platonov, P.G.
Abstract: Aim: Ventricular fibrillation (VF) during reperfusion in ST-elevation myocardial infarction (STEMI) is associated with increased in-hospital mortality. Dispersion of ventricular repolarization contributes to ventricular vulnerability during ischemia. Tpeak -Tend interval was proposed as a ventricular repolarization dispersion marker, however its value for prediction of reperfusion VF remains uncertain. We aimed to assess whether Tpeak -Tend before PCI in STEMI is associated with reperfusion VF. Methods: STEMI patients admitted for primary PCI were retrospectively assessed for VF during reperfusion. Pre-PCI ECGs recorded in 40 patients with reperfusion VF (rVF group; age 65 ± 13 years, 80% male) were compared with 374 consecutive patients without reperfusion arrhythmias (No-rVF group; age 67 ± 12 years; 68% male). Digital ECGs were automatically processed and Tpeak -Tend interval computed on a per-lead basis. The global Tpeak -Tend was calculated between the earliest Tpeak and the latest Tend in any lead, and tested for association with reperfusion VF using logistic regression analysis. Results: The leftward shift of Tpeak toward QRS complex in ischemic leads resulted in Tpeak -Tend prolongation. Global Tpeak -Tend in rVF group was higher than in No-rVF group (142 ± 24 vs 130 ± 27 ms; p = 0.007). Global Tpeak -Tend ≥ 131 ms predicted reperfusion VF (OR = 3.41; 95% CI 1.66–7.04; p = 0.001) and remained a significant predictor of reperfusion VF in multivariable analysis. Conclusion: Tpeak -Tend interval before PCI in STEMI was an independent predictor of reperfusion VF. Our findings warrants further research aimed at prospective validation of Tpeak -Tend as a marker of periprocedural arrhythmic risk. Highlights: The study has shown that the Tpeak -Tend before PCI in STEMI is associated with VF during reperfusion. The prolongation of Tpeak -Tend is due to T peak shift toward to QRS onset in infarct-related leads. Further research is needed aimed at prospective validation of Tpeak -Tend as a marker of periprocedural arrhythmic risk.